Fading and residual responses for thermoluminescent dosimetry of silica beads irradiated using a high-dose electron-beam. (May 2021) - Ley, K.; Hashim, S.A.; Lohstroh, A.; Shenton-Taylor, C.; Bradley, D.A.
Abstract: Thermoluminescent (TL) glow-curves of 10 different coloured Toho Japan bead types have been obtained using a Ris ø TL/OSL reader studied for a fading period of 6 months as well as for residual dosimetry for fading up to 16 months after irradiation. For the entirety of the delay period studied the Frosted beads showed the largest TL response followed by Pink and Rose beads. Pink beads showed the best fit to the second order polynomial fit applied to the observed fading. In a more detailed dose curve fitted for a 6 month delay between irradiation and readout in order to determine the nature of the TL response as a function of increasing dose, it was found to follow the same trend for all bead colours. The residual TL response was also studied for beads that showed a large TL response. In these studies all colours showed similar dose response curves to those for the 1 st readout, with Pink beads showing the best agreement to the fit applied to model fading. Highlights: TL response measured for electron beam irradiation of 1 kGy to 250 kGy, for 10 colours of beads. The fading effect on TL response was studied in depth for Pink beads over a 16-month period. Greatest TL produced from Pink and Frosted beads, Green and Lime beads show no correlation. A detailed comparison of dose dependence with a 6 month fading time was evaluated for Pink beads. All beads were evaluated for residual dosimetry at a fading time of 3 weeks.